Legitimizing the Post-Socialist Transformation in Romania - Țoc, Sebastian (Calitatea Vieții, 2018)
In this article I argue that political decisions in the Romanian post-socialist era have been tacitly accepted by the population mainly because political actors legitimized them through a “breaking up” with the communist past and through the projection of a future Romanian society which has a similar level of development as Western countries. Therefore, an official discourse, in which political decisions that generated major social costs were “necessary and inevitable” for the construction of an advanced capitalist society, was employed. In the first part of the paper, I describe the economic situation of Romania at the beginning of the transition process (1990) and the official strategies proposed for a successful transition. In the second part of the article, I discuss the processes of justification and legitimization of the economic reform and the involvement of international organizations such as the International Monetary Fund (IMF) or the World Bank (WB). In the last part, the article focuses on the results of political decision-making in the transition period, mainly discussing the primary consequences that affected the population.